Biomimetic hydrogels with mesoscale collagen architecture for patient-derived tumor organoids culture - Jiaxin Wang; Zhilin Sui; Wei Huang; Zhentao Yu; Ling Guo (Bioactive Materials, 2024)
Patient-derived tumor organoids (PDTOs) shows great potential as a preclinical model. However, the current methods for establishing PDTOs primarily focus on modulating local properties, such as sub-micrometer topographies. Nevertheless, they neglect to capture the global millimeter or intermediate mesoscale architecture that have been demonstrated to influence tumor response to therapeutic treatment and tumor progression. In this study, we present a rapid technique for generating collagen bundles with an average length of 90 ± 27 μm and a mean diameter of 5 ± 1.5 μm from tumor tissue debris that underwent mechanical agitation following enzymatic digestion. The collagen bundles were subsequently utilized for the fabrication of biomimetic hydrogels, incorporating microbial transglutaminase (mTG) crosslinked gelatin. These biomimetic hydrogels, referred to as MC-gel, were specifically designed for patient-derived tumor organoids. The lung cancer organoids cultured in MC-gel exhibited larger diameters and higher cell viability compared to those cultured in gels lacking the mesoscale collagen bundle; moreover, their irregular morphology more closely resembled that observed in vivo. The MC-gel-based lung cancer organoids effectively replicated the histology and mutational landscapes observed in the original donor patient’s tumor tissue. Additionally, these lung cancer organoids showed a remarkable similarity in their gene expression and drug response across different matrices. This recently developed model holds great potential for investigating the occurrence, progression, metastasis, and management of tumors, thereby offering opportunities for personalized medicine and customized treatment options.